National Health Service : deputation to Minister of Health on 17 June 1946 (report) - Bevan, Aneurin, 1897-1960
1946-06-25 1946 1940s 9 pages -7- ment of medicine at the Health Centre. Administration Regarding the T.U.C. claim for representation of health workers on ad hoc committees under the scheme he said that he did not think that their policy could be carried through merely by having one or two people on a committee. He considered that in that way the position of those people became invidious. He would prefer there to be a staff organisation in which the whole body of workers were participating in the administration instead of one or two representatives only. If a healthy industrial democracy was to be achieved, then the men and women taking part in the new service should participate in the making of policy. That might in fact be thwarted by having one or two representatives on a committee. To have a worker on the employing body would produce a dichotomy in the service. That problem had not yet been solved within the Trade Union Movement, i.e. how it was possible for a person to be represented on a body from which he himself derived favours and still remain representative was still a problem. MISS WESTMACOTT said that it was particularly hurtful to find doctors represented on the committees all the way through but with no representation of the nurses. However good the doctors were, they could not carry on without the nurses. The only representative of the nurses was the Matron and the Trade Union Movement could not be satisfied with such representation. MR. BEVAN said that the reason for the doctors being represented was not to give them participation in the administration of the service but because they were concerned with health in general. All the specialised services would be catered for by specialised committees. He had taken power in the Bill to establish advisory committees on nursing, the domestic side, pharmacy, dentistry, ophthalmology, gynaecology. All those committees would report direct to the Minister as well as to the Central Health Services Council. They would be advisory bodies in their own right and proper place. DR. GORDON WARD said that a very great number of nurses was needed and their credit would be spoilt if they were to have little representation in the service. MR. BEVAN said that he did not think that he would get a single additional nurse recruited because they had representation on the Central Health Services Council. MR. ALLEN said that the psychological effect of these things was important. MISS WESTMACOTT said that it would help considerably if the nurses representation was raised from 2 to 5. MR. BEVAN said that nurses' salaries had been increased, and it was hoped to get their conditions improved. Even more important, however, was to get nurses away from the influence of the Matron. Tenure of Office on Central Council He said that he was not hostile to the T.U.C. suggestion of five years for tenure of office. He just did not want to put it in the Bill. Regional Hospital Boards - Remuneration and Conditions of Officers The Minister said that regulations would have to be made by 292/847/4/113